Pemikiran Pendidikan Ibnu Sina sebagai Model Integratif dalam Peningkatan Mutu Pendidikan Islam Masa Kini - Wauran, Meissara Putri Andannari; Khoir, Mulyanto Abdulloh (TSAQOFAH, 2025)
Ibn Sina’s educational thought holds strategic relevance in addressing the quality challenges of Islamic education in the contemporary era, particularly concerning the weak integration of intellectual and spiritual dimensions within current educational systems. This study aims to explore Ibn Sina’s concept of integrative education and evaluate its potential as a model for improving the quality of Islamic education. A qualitative approach was employed through library research, using descriptive and hermeneutic analysis of Ibn Sina’s key works. The findings reveal that Ibn Sina’s educational philosophy emphasizes the integration of reason and revelation, theory and practice, and a balanced development between intellectual achievement and character formation. Education, according to Ibn Sina, is not solely aimed at developing rational potential, but also at shaping a holistic personality grounded in spiritual values. The study concludes that Ibn Sina’s integrative educational model provides a robust philosophical and pedagogical foundation for constructing a holistic and high-quality Islamic education system. Its implications underscore the urgency of applying Ibn Sina’s educational values in curriculum reform and instructional strategies in today’s Islamic educational institutions.